Essentials of cloud computing - Chandrasekaran, K. (CRC Press LLC, 2015)
Cloud computing-accessing computing resources over the Internet-is rapidly changing the landscape of information technology. Its primary benefits compared to on-premise computing models are reduced costs and increased agility and scalability. Hence, cloud computing is receiving considerable interest among several stakeholders-businesses, the IT industry, application developers, researchers, and students. To successfully embrace this new computing model, these stakeholders need to acquire new cloud computing skills and knowledge. This book is designed to provide readers with a clear and thoroug.